Factors associated with the prevalence of anterior open bite among preschool children: A population-based study in Brazil - Daniella Borges Machado; Valéria Silva Cândido Brizon; Gláucia Maria Bovi Ambrosano; Davidson Fróis Madureira; Viviane Elisângela Gomes; Ana Cristina Borges de Oliveira (Dental Press Editora, 2014)
INTRODUCTION: The aim of this study was to identify factors associated with the prevalence of anterior open bite among five-year-old Brazilian children. METHODS: A cross-sectional study was undertaken using data from the National Survey of Oral Health (SB Brazil 2010). The outcome variable was anterior open bite classified as present or absent. The independent variables were classified by individual, sociodemographic and clinical factors. Data were analyzed through bivariate and multivariate analysis using SPSS statistical software (version 18.0) with a 95% level of significance. RESULTS: The prevalence of anterior open bite was 12.1%. Multivariate analysis showed that preschool children living in Southern Brazil had an increased chance of 1.8 more times of having anterior open bite (CI 95%: 1.16 - 3.02). Children identified with alterations in overjet had 14.6 times greater chances of having anterior open bite (CI 95%: 8.98 - 24.03). CONCLUSION: There was a significant association between anterior open bite and the region of Brazil where the children lived, the presence of altered overjet and the prevalence of posterior crossbite.